Fibroblast Growth Factor Receptor 3 Inhibits Osteoarthritis Progression in the Knee Joints of Adult Mice. Issue 10 (28th September 2016) - Tang, Junzhou; Su, Nan; Zhou, Siru; Xie, Yangli; Huang, Junlan; Wen, Xuan; Wang, Zuqiang; Wang, Quan; Xu, Wei; Du, Xiaolan; Chen, Hangang; Chen, Lin
Abstract : Objective: Fibroblast growth factor (FGF) signaling is involved in articular cartilage homeostasis. This study was undertaken to investigate the role and mechanisms of FGF receptor 3 (FGFR‐3) in the pathogenesis of osteoarthritis (OA) caused by surgery and aging in mice. Methods: FGFR‐3 was conditionally deleted or activated in articular chondrocytes in adult mice subjected to surgical destabilization of the medial meniscus (DMM). A mouse model of human achondroplasia was also used to assess the role of FGFR‐3 in age‐associated spontaneous OA. Knee joint cartilage was histologically evaluated and scored using the Osteoarthritis Research Society International system. The expression of genes associated with articular cartilage maintenance was quantitatively evaluated in hip cartilage explants. The effect of inhibiting Indian hedgehog (IHH) signaling in Fgfr3 ‐deficient explants was analyzed. Results: Conditional Fgfr3 deletion in mice aggravated DMM‐induced cartilage degeneration. Matrix metalloproteinase 13 and type X collagen levels were up‐regulated, while type II collagen levels were down‐regulated, in the articular cartilage of these mice. Conversely, FGFR‐3 activation attenuated cartilage degeneration induced by DMM surgery and age. IHH signaling and runt‐related transcription factor 2 levels in mouse articular chondrocytes were up‐regulated in the absence of Fgfr3, while inhibition of IHH signaling suppressed the increases in the expression of Runx2, Mmp13, and other factors in Fgfr3 ‐deficient mouse cartilage explants. Conclusion: Our findings indicate that FGFR‐3 delays OA progression in mouse knee joints at least in part via down‐regulation of IHH signaling in articular chondrocytes.